A model-driven framework for multi-paradigm modeling and holistic simulation of healthcare systems. (March 2018) - Djitog, Ignace; Aliyu, Hamzat O; Traoré, Mamadou K
The domain of healthcare is characterized by a high degree of complexity and a diversity of perspectives, and modelers are often confronted with the challenge of formulating a simulation model that captures this complexity in a systematic and manageable manner. Most often, the diverse perspectives of healthcare systems are studied in isolation and using specific formalisms. As it turns out, answering questions concerning behavioral properties of the overall system becomes difficult and therefore not sufficient for an efficient design and analysis of the system under study. In this article, we propose a framework for multi-paradigm modeling and holistic simulation of healthcare systems. We present a modeling methodology with a plethora of formalisms to allow the modeler to choose an appropriate formalism at a given level of abstraction while model transformation relates the different formalisms. Furthermore, we develop an integrative approach for the interactions between models of different perspectives through dynamic update of model output-to-parameter integration during concurrent simulations. Such an approach provides multiple levels of explanation for the same system, while offering, at the same time, an integrated view of the whole. The framework has successfully been applied to study part of the Nigerian healthcare system.